Ammonia amendment promotes high rate lactate production and recovery from semi-continuous food waste fermentation. (April 2020) - Zhang, Wenjuan; Li, Xiang; He, Ya; Xu, Xianbao; Chen, Hong; Zhang, Ai; Liu, Yanan; Xue, Gang; Makinia, Jacek
Graphical abstract: Highlights: Ammonia nitrogen addition increased the yield of lactic acid in mesophilic reactors. High rate lactate production could be recovered by adding ammonia in Ctrl reactors. Appropriate ratio of FAN and ammonia ion is the key for high lactate production. Ammonia nitrogen promotes solubilization, hydrolysis, glycolysis and acidification. Relative abundances of microbes responsible for lactate production were proliferated. Abstract: In this study, a reliable approach using ammonia nitrogen was proposed to increase lactate production during semi-continuous food waste (FW) fermentation under mesophilic conditions. Both free ammonia nitrogen (FAN) and ammonium ion (NH4 + -N) were present in mesophilic reactors, with a wide FAN/NH4 + -N ratio variation due to the intermittent pH control. The investigation of responsible mechanisms revealed that the increased production yield of LA was associated with the acceleration of solubilization, hydrolysis, glycolysis and acidification. The presence of FAN and NH4 + -N in proper concentrations increased lactate production by 2.4 folds and recovered lactate production to 24.5 g COD/L from low rate control reactor (9.6 g COD/L) under mesophilic conditions. Furthermore, the microorganisms responsible for LA accumulation ( Bavariicoccus, Enterococcus, Bifidobacterium and Corynebacterium ) were selectively enriched, and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways associated with carbohydrate transport and LA production were enhanced in nitrogen fed reactors.